Selection of the Optimal Concentration of Nitro Blue Tetrazolium Dye in Polyvinyl Alcohol Film for Diagnostic Radiology - Albejadi, Reham; Ullah, Zabih; El-Taher, Atef; Alashrah, Saleh (Trends in Sciences, 2024)
Ensuring the limited exposure of both patients and medical professionals to radiation during examinations is paramount. One effective approach is the utilization of a film dosimeter that is not only efficient but also easy to carry. In this research, we employed polyvinyl alcohol/nitro blue tetrazolium (PVA/NBT) with varying concentrations of NBT dye (ranging from 0.015 to 0.3 g) to identify the most optimal concentration. These films were subjected to low doses of gamma rays (8, 25, 55 and 96 mGy) emitted from 3 Cs-137 sources. XRF analysis confirmed the effectiveness of the preparation method used, and the NBT salt exhibited excellent solubility (R2 = 0.93). The films exhibited an increasing yellow hue as the concentration of NBT dye rose. Following irradiation, they took on a yellowish-brown tint, intensifying with higher gamma doses. PVA/NBT films, when stored in the dark, demonstrated good stability for 30 days post-irradiation. Analysis using ImageJ software unveiled that the relative density of the red color heightened proportionally with the concentration of NBT dye. XRD patterns showcased the clarity of structural rearrangements occurring after irradiation with high NBT concentrations. Two distinct peaks were registered at 2θ = 20.12 and 40.94 °, which shifted to 2θ = 19.74 and 41.30 ° post-gamma irradiation. The CIELab system study and K/S color strength indicated that increasing the NBT dye concentration led to a linear rise in color strength with escalating low gamma doses. Through a comprehensive assessment, it is concluded that PVA/NBT film can be effectively employed as a dosimeter for low gamma doses in diagnostic radiology. HIGHLIGHTS Nine different concentrations of NBT dye were used to prepare PVA/NBT films. The standard dose scale in diagnostic radiology (mGy) was applied in this work. CIELab system parameters showed a linear increase with increasing applied dose. XRD pattern recorded a shifted peak after irradiation from 2θ = 20.12 to 19.74 °. The dose-response was affected by increasing the NBT dye to a certain concentration. GRAPHICAL ABSTRACT